Patient Burden with Current Surveillance Paradigm and Factors Associated with Interest in Altered Surveillance for Early Stage HPV‐Related Oropharyngeal Cancer. (29th April 2021) - Gharzai, Laila A.; Burger, Nicholas; Li, Pin; Jaworski, Elizabeth M.; Henderson, Caitlin; Spector, Matthew; Rosko, Andy; Chen, Michelle M.; Prince, Mark E.; Bradford, Carol R.; Malloy, Kelly M.; Stucken, Chaz L.; et al.
Abstract: Introduction: Optimal surveillance paradigms for survivors of early stage human papillomavirus (HPV)‐related oropharyngeal cancer are not well defined. This study aimed to characterize patient interest in and factors associated with an altered surveillance paradigm. Materials and Methods: We surveyed patients with Stage I or II HPV‐related oropharyngeal cancer treated at a tertiary care institution from 2016 to 2019. Primary outcomes were descriptive assessment of patient knowledge, interest in altered surveillance, burdens of in‐person appointments, and priorities for surveillance visits. Ordinal regression was used to identify correlates of interest in altered surveillance. Results: Sixty‐seven patients completed surveys from February to April 2020 at a median of 21 months since completing definitive treatment. A majority (61%) of patients were interested in a surveillance approach that decreased in‐person clinic visits. Patients who self‐identified as medical maximizers, had higher worry of cancer recurrence, or were in long‐term relationships were less likely to be interested. Patients reported significant burdens associated with surveillance visits, including driving distance, time off work, and nonmedical costs. Patients were most concerned with discussing cancer recurrence (76%), physical quality of life (70%), mortality (61%), and mental quality of life (52%) with their providers at follow‐up visits. Conclusion: Patients with early stage HPV‐related oropharyngeal cancers are interested in altered surveillance approaches, experience significant burdens related to surveillance visits, and have concerns that are not well addressed with current surveillance approaches, including physical and mental quality of life. Optimized surveillance approaches should incorporate patient priorities and minimize associated burdens. Implications for Practice: The number of patients with HPV‐related oropharyngeal cancers is increasing, and numerous clinical trials are investigating novel approaches to treating these good‐prognosis patients. There has been limited work assessing optimal surveillance paradigms in these patients. Patients experience significant appointment‐related burdens and have concerns such as physical and mental quality of life. Additionally, patients with early stage HPV‐related oropharyngeal cancers express interest in altered surveillance approaches that decrease in‐person clinic visits. Optimization of surveillance paradigms to promote broader survivorship care in clinical practice is needed. Abstract : Patient input is critical to improve surveillance options for human papillomavirus (HPV)‐related oropharyngeal cancer. This article assesses patient interest in and factors associated with alternative surveillance approaches, including patient knowledge, burdens of in‐person appointments, and priorities for follow‐up visits.